APPLICATION EFFECT OF SPUTUM INDUCTION BY ACETYLCYSTEINE AEROSOL INHALATION IN THE DIAGNOSIS OF PULMONARY TUBERCULOSIS IN CHILDREN - JI Xueqin, CHU Yan, JI Hailing, LI Tongxia (精准医学杂志, 2023)
Objective To investigate the application effect of aerosol inhalation of acetylcysteine in the diagnosis of pulmonary tuberculosis in children. Methods A total of 180 children suspected of pulmonary tuberculosis who were admitted to Qingdao Chest Hospital were enrolled and randomly divided into control group, bronchoscopy group, and acetylcysteine group. For the control group, routine sputum examination (including concentrated smear method, culture method, and GeneXpert test) was performed to identify Mycobacterium tuberculosis; for the bronchoscopy group, routine sputum examination combined with collection of alveolar lavage fluid by bronchoscopy was performed to identify Mycobacterium tuberculosis; for the acetylcysteine group, routine sputum examination combined with collection of sputum after aerosol inhalation of acetylcysteine was performed to identify Mycobacterium tuberculosis. The three groups were compared in terms of the detection rate of Mycobacterium tuberculosis in sputum or alveolar lavage fluid and the incidence rate of adverse reactions. Results There was a significant difference in the detection rate of Mycobacterium tuberculosis between the control group, the bronchoscopy group, and the acetylcysteine group (χ2=9.850,P<0.05); there was a significant difference between the control group and the bronchoscopy group and between the control group and the acetylcysteine group (χ2=8.889,6.009,P<0.05), while there was no significant difference between the bronchoscopy group and the acetylcysteine group. There was a significant difference in the incidence rate of adverse reactions between the control group, the bronchoscopy group, and the acetylcysteine group (χ2=27.705,P<0.05), and there was also a significant diffe-rence between any two groups (χ2=7.685-25.455,P<0.05). Conclusion Sputum induction by acetylcysteine aerosol inhalation can significantly improve the diagnostic rate of pulmonary tuberculosis in children, and there is no significant change in the detection rate of Mycobacterium tuberculosis after the additional use of bronchoscopy, but it can protect children from the pain caused by bronchoscopy with a relatively low incidence rate of adverse reactions. Therefore, it holds promise for further clinical application.